Development of Achievement Test on Statistical Application and Interpretation for Assessing Learning of Educational Researchers Through Module - Tyagi, S. K. (JOURNAL OF INDIAN EDUCATION, 2019)
In the backdrop of University Grants Commission’s (UGC) decision to relax the eligibility criteria for research guides, need was felt to augment the educational researchers’ skills in statistical application and interpretation through the module. Apart from developing a module on the subject, it was planned to develop an achievement test to assess the effect of treatment in terms of researchers’ understanding of the statistical application and writing interpretation of the results. Accordingly, an achievement test was constructed in two parts. Part A focused on the assessment of understanding of statistical tests and appropriate research situations, it comprised of 50 multiple choice type test items. Part B, consisting of 10 free response test items tested researchers’ skill of interpreting results of the statistical tests. The tests were reviewed by the experts of research methodology and testing. The reviewed tests were tried out on a small sample of 18 researchers of different universities participating in two research methodology workshops at University of Allahabad and Regional Institute of Education (RIE), Ajmer respectively. Response analysis of the test items was performed. The feedback obtained from the response analysis led to the needed item modification and item replacement. Cronbach’s α was computed following the final administration of the test.